Redistribution with Unequal Life Expectancy - Sebastian Koehne (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper introduces life expectancy inequality into a tractable Mirrleesian life-cycle model and characterizes the optimal income tax policy using theory and calibration. A positive association between life expectancy and income counteracts the well-known static pattern of declining marginal utility. As a result, the mechanical value of redistribution is reduced at all income levels. Moreover, the pension wedge becomes a novel determinant of optimal taxation, motivating relatively lower optimal tax rates for low earners and relatively higher optimal tax rates for high earners. Quantitatively, the effects of the mechanical value of redistribution dominate, and the optimal marginal tax rates fall by up to 10 percentage points when life expectancy is heterogeneous.
Keywords: D82; H21; 330; optimal taxation; redistribution; life expectancy; inequality